Heroes And Antiheroes As Victims Of Abuse In The Harry Potter Series - Saleh, Maysam Bahaa (2011)

(untitled)
In children’s literature various themes have been examined in connection with violence such as abuse and bullying. Charles Dickens’ Oliver Twist and Roald Dahl’s James and the Giant Peach are examples of children’s suffering since the main characters are orphans living in a violent world and who are, at the same time, victims of abuse. The Harry Potter series are no exception. Since the first book of the series, Harry Potter and the Philosopher’s Stone (1997), until the seventh book Harry Potter and the Deathly Hallows (2007) J.K. Rowling pursued the theme of child abuse through her depiction of three characters: Harry Potter, Severus Snape and Lord Voldemort by using different types of abuse such as the physical abuse, emotional abuse, verbal abuse, bullying, mobbing and neglect.